Effects of irradiation on the survival of bacterial contaminants in food - Lily Natalia; A. Priadi; Z. Irawati (Jurnal Ilmu Ternak dan Veteriner, 2009)
The primary concern about microbial safety of irradiated food is the survival of pathogenic spore forming bacteria. Clostridium sporogenes was selected as the spore forming test organism for conducting inoculated pack studies for its similarities to the most toxigenic Cl. botulinum, in radiation resistance. Minimum radiation dose applied (45 kGy under cryogenic condition, in -790C) was determined to eliminate Cl. sporogenes spores and other bacterial contaminants in different kind of Indonesian chicken and beef dishes. In separate studies, irradiation doses of 3 – 7 kGy at cryogenic condition was used to improve the microbiological safety of a number chilled prepared meals. The dishes or ready to eat foods were packaged in air impermeable pouches. Irradiation process was carried out after inoculation on chicken and beef dishes with certain amounts of Cl. sporogenes spores. The evaluation of colony count differences between the irradiated and unirradiated foods revealed the effect of radiation on the survival of bacterial spores or other bacterial contaminants. It was demonstrated that a minimum dose of 45 kGy under cryogenic condition eliminated the spore of Cl. sporogenes, Bacillus spp and Staphylococcus spp. Irradiation at doses 5-7 kGy significantly reduced some potential pathogenic microorganisms in samples without affecting quality up to 3 months of storage at the refrigeration temperature. Key Words: Food Safety, Irradiation, Bacterial Contaminants